SEX DIFFERENCES OF VLF100 AND VLF50 SPECTRUM OF HEART RATE VARIABILITY IN HEALTHY INDIVIDUALS OF YOUNG AGE AND OLDER SUBJECTS WITH VASCULAR PATHOLOGY IN TERMS OF SEVEN-TEST, HYPERVENTILATION AND ORTHOSTASIS - Арнольд Наумович Флейшман; Татьяна Валентиновна Кораблина; Игорь Германович Халиулин; Станислав Альфредович Петровский; Артем Андреевич Неретин (Медицина в Кузбассе)
Subject. About minute rhythms of heart rate variability (HRV) (VLF100 and VLF50) and their role in sex differences of HRV and autonomic provision of the body.